Suplementasi Tryptophan dan Treonine Pada Level Protein Kasar Berbeda Dalam Pakan Terhadap Dimensi Tubuh Ayam Kampung Fase Pullet - Charles V. Lisnahan; Oktovianus R. Nahak; Stefanus Kolo (Program Studi Peternakan, Fakultas Pertanian, Universitas Timor, 2021)
This study aims to determine the effect of giving tryptophan + threonine amino acids and different levels of crude protein on body dimensions of free-range chickens in the pullet phase. This research was carried out in Sasi sub-district, Kefamenanu City District, North Central Timor Regency, for 8 weeks from October-December 2020. This study used 120 free-range chickens aged 14 weeks, designed with a completely randomized design with a 2 x 3 factorial pattern, namely 2 amino acid levels and 3 levels of crude protein. Each treatment combination was repeated 4 times. The treatments were: A1C1 (threonine 0.75% + tryptophan 0.15% + protein 15%), A1C2 (threonine 0.75% + tryptophan 0.15% + protein 17%), A1C3 (threonine 0.75% + tryptophan 0.15% + protein 19%, A2C1 threonine 1.00% + tryptophan 0.20% + protein 15%), A2C2 (threonine 1.00% + tryptophan 0.20% + protein 15%), A2C3 (threonine 1.00% + tryptophan 0.20% + 19% protein. The variables observed in this study were body weight, body length, chest circumference, chest v-bone length, upper thigh length, lower thigh length, shank length, shank circumference, and finger length. The data obtained were analyzed using analysis of variance and Duncan's multiple distance test. Statistical analysis showed that the amino acids threonine and tryptophan had a significant (P<0,05) effect on body weight, body length, chest circumference, chest v-bone length, upper thigh length and lower thigh length, while crude protein level significantly affected body weight, body length, chest circumference, chest v-bone length, upper thigh length, lower thigh length. In this study, there was an interaction between amino acids and crude protein levels on the body weight and finger length of free-range chickens. It was concluded that the crude protein level of 19% could increase body weight, body length, chest circumference, chest v-bone length, femur length, and maximal pullet phase tibia length of free-range chickens; Amino acid levels of threonine 1.00% and tryptophan 0.20% increased body weight, body length, chest circumference, chest v-bone length, femur length, tibia length of pullet phase chickens; The combination of 19% crude protein level + 1.00% threonine amino acid and 0.20% tryptophan can increase the bodyweight of free-range chickens in the pullet phase.